The negative impact of lameness on dairy cow reproduction. (29th July 2022) - Tsousis, Georgios; Boscos, Constantinos; Praxitelous, Anastasia
Abstract: Lameness in modern dairy farms is a prevalent disorder that negatively affects all aspects of production. Additionally, is a prevailing contributor to the decreased welfare of cows. Recent research has added valuable knowledge on the negative impacts of lameness on dairy cow reproduction. Lame cows have marked behavioural changes, as well as increased inflammatory and stress indicators compared to healthy herd mates. As a result, the functioning of the hypothalamus–pituitary–ovarian axis is significantly affected and leads to suppressed reproductive performance. Lame cows seem to be more prone to uterine infections post‐partum, experience higher levels of negative energy balance, resume ovarian cyclicity to a lower proportion during puerperium and show decreased potential to conceive and higher pregnancy losses. Hormonal treatments of lame cows compensate for some of these disturbances yet fail to fully restore fertility potential. From the available scientific literature is apparent that compromised fertility due to lameness can only be achieved through prevention and prompt diagnosis and treatment of lame cows.